Pengaruh Instrumen Makroekonomi Terhadap Konsumsi di Indonesia - M Rasyidin; M Saleh; Azka Rizkina (TIN: Terapan Informatika Nusantara, 2023)
This research aims to examine the mediating influence of exchange rates between macroeconomic instruments such as inflation, interest rates and capital flows on financial market performance. The data in this research is a time series from 1992 – 2022 using the Path Analysis model. The results of this research conclude that inflation and interest rates have an insignificant effect on the exchange rate. Meanwhile, capital flows have a significant influence on the exchange rate in Indonesia. Inflation, interest rates and exchange rates have no significant effect on financial market performance in Indonesia. Capital flows have a significant effect on financial market performance. Inflation has a significant effect on financial market performance through the exchange rate. Interest rates have no significant effect on financial market performance through exchange rates. Furthermore, capital flows have a significant effect on financial market performance through exchange rates